EDUCAÇÃO INFANTIL EM TEMPOS DE PANDEMIA: ENTRE O ABANDONO AO DOCENTE E A INVISIBILIDADE DA CRIANÇA DE 0 A 3 ANOS - MACHADO, LEANDRA SOUZA (2022)
In 2020 the world was surprised by the COVID-19 pandemic (disease caused by the new coronavirus, called SARS-COV-2), which motivated a series of recommendations from health agencies, including social distancing, a condition that led to the closure of several different institutions, among these schools. Given this scenario, new referrals had to be adopted by teachers, including early childhood education. Based on the recognition that practices in Early Childhood Education occur through rich experiences from interactions between children with their peers, based on play and welcoming, the problem of this research is defined as this: How did the teaching work in Early Childhood Education develop during the pandemic and what difficulties were faced by teachers? Thus, we indicate as a general objective to recognize how it was performed and what challenges were part of teaching in Early Childhood Education in times of pandemic, in the context of the Municipal Centers of Early Childhood Education in the municipality of Guarapuava-Pr. As specific objectives we listed: to understand the objectives and purposes of Early Childhood Education; recognize the specificities of teaching with children from 0 to 3 years of age; identify actions developed 'remotely' for the public of Early Childhood Education and; to investigate the difficulties of teachers in teaching in this stage in the face of the pandemic context. Methodologically, this is a qualitative and exploratory research, which conducted semi-structured interviews with teachers of Municipal Centers of Early Childhood Education (CMEIs) in the city of Guarapuava, in the state of Paraná, which were recorded and transcribed. The results obtained indicate that, in an attempt to maintain links with children and their families, and following the guidelines of municipal management, the 'remote' activities were adopted in Early Childhood Education during the emergency period established by the pandemic. This strategy, on the one hand, was the way found to maintain contact with children, but, on the other hand, represented a setback and a break with the purposes and objectives of the stage, since Early Childhood Education occurs through daily relationships through which children and adults share experiences, experiences and concerns producing child culture. Moreover, since teaching with young children is done in relationships, virtuality imposed mass and unfound practices among teachers, children and their families. The teachers manifested many difficulties, especially focused on access and use of technology and digital devices, work overload, insufficient institutional support and little return of families, unburdening a reality of exclusions and suffering for those involved.